PEMBINAAN KAUM LESBI DI KOTA MAKASSAR (STUDI TENTANG METODE DAKWAH MAUIDZA HASANAH) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
AbstarkThe results of this study indicate that the problematic lesbians in Makassar City are caused by family relationships, namely parents and children who are not harmonious, which then causes the child to feel unattended and affectionate. In addition, the influence of a bad environment also affects a person to behave in accordance with what dominates around him and those who experience domestic violence (KDRT). Bad experiences in the past lead to disappointment, so choosing same-sex partners to avoid the same treatment. The application of the method of da'wah mauidza hasanah to lesbi in Makassar City includes advice and tabsyir wa tandzir. Advice is very important to do because it becomes one of the supports so that lesbi behavior can be improved. In this case what is most needed is the role of family, close friends and scholars. Whereas tabsyir wa tandzir is the delivery of da'wah which contains good news for people who follow the preaching. The good news that is delivered can be used as a benchmark for change. In addition, the form that contains motivation will reduce frustration in the community, especially for lesbi people.